Reasoned opinion on the modification of the existing MRLs for difenoconazole in various crops - European Food Safety Authority (EFSA Journal, 2013)
In accordance with Article 6 of Regulation (EC) No 396/2005, France, herewith referred to as the evaluating Member State (EMS), received an application from Syngenta AGRO S.A.S. to modify the existing MRLs for the active substance difenoconazole in a wide range of crops. In order to accommodate for the intended European uses on quinces, several root crops, bulb vegetables, cucurbits (inedible peel), witloof chicory, globe artichokes, rice and chicory roots and to accommodate the authorized use in Brazil on papaya, the EMS proposed to raise the existing MRLs for difenoconazole in all these crops. The EMS drafted an evaluation report according to Article 8 of Regulation (EC) No 396/2005, which was submitted to the European Commission and forwarded to EFSA. According to EFSA the data are sufficient to derive MRL proposals for all the crops considered. The applicant has not submitted data on TDM residues in the crops under consideration. Based on the risk assessment results, EFSA concludes that the intended use of difenoconazole on the crops under consideration will not result in a consumer exposure exceeding the toxicological reference values for difenoconazole and therefore is unlikely to pose a public health concern. The consumer risk assessment regarding the TDMs was not undertaken in the framework of the current application and has to be performed as soon as the confirmatory data for triazole pesticides are available and a suitable risk assessment methodology has been developed, taking into account the contribution of the TDMs present in primary crops, rotational crops, processed commodities and products of animal origin resulting from different triazole pesticides.